Design and Study on Online Software Defined Networking Controller Performance Monitor - Xufu Huang; Chuan Liu; Yilei Lin; Yaohui Jin; Xuan Luo (Dianxin kexue)
With network scale and network traffic growing up，the performance of SDN controller can probably be bottleneck，in order to still obtain correct performance status on dynamical workload，an online performance monitor frame was designed and Lpdex，a controller latency performance metric，was defined. Then a simple prototype of performance monitor was implemented on FloodLight，a widely used controller，after experimental evaluation，controller performance monitor was validated feasible and Lpdex can indicate controller latency performance accurately online with workload varying.